Florence Nightingale : the courageous life of the legendary nurse - Reef, Catherine (Clarion Books, 2017)
"A biography for young adult readers on Florence Nightingale, the pioneering nurse best known for her work during the Crimean War, where she rectified horrifying conditions and made nightly rounds to check on patients, saving hundreds of lives and sparking worldwide healthcare reform"--